What is standard care for people with learning disabilities and behaviour that challenges and what does it cost?. (17th June 2016) - Iemmi, Valentina; Knapp, Martin; Gore, Nick; Cooper, Vivien; Brown, Freddy Jackson; Reid, Caroline; Saville, Maria; ,
Abstract : Accessible summary: The provision of care and support for people with learning disabilities and behaviour that challenges in England is mixed. Children and young people with learning disabilities and behaviour that challenges are likely to live within the community, while adults will be in residential care. Overall, supporting people with learning disabilities and behaviour that challenges within the community is likely to be less expensive than supporting them in residential care. Abstract: Background: We describe current care arrangements in England for children, young people and adults with learning disabilities and behaviour that challenges, and estimate their comparative costs. Materials and Methods: A two‐round Delphi exercise was performed in March and April 2014, followed by a costing exercise. Results: The study finds a mixed picture: participants reported that 60–87% of children, 66–88% of young people and 34–47% of adults were likely to be living within the community. Annual cost of care would range between £39 612 and £74 876 for children, between £35 235 and £52 832 for young people and between £81 478 and £94 799 for adults. Conclusion: While residential‐based care may continue to be necessary for respite or for individuals with particular needs, community‐based care may be an economically attractive alternative, supporting the inclusion of people with learning disabilities and behaviour that challenges within their communities, potentially at a lower cost.